2000
DOI: 10.2174/1381612003400498
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Effects of 1,25-Dihydroxyvitamin D3 and Vitamin D Analogs

Abstract: The role of 1,25-dihydroxyvitamin D3 (1,25-(OH)2D3) as a regulator of cell growth and differentiation is well recognized. Currently, 1, 25-(OH)2D3 and vitamin D analogs are being evaluated for their therapeutic potential in the treatment of hyperproliferative disorders like cancer. In the present review, we will discuss several processes that might be involved in 1,25-(OH)2D3- and vitamin D analog-mediated suppression of cancer cell growth. The effects on tumor cell proliferation, differentiation, apoptosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
4

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 136 publications
0
34
0
4
Order By: Relevance
“…28) Many vitamin D analogues showed anti-cancer activity in vitro using human cultured cell lines, however, some of them did not possess such activity in vivo. 29,30) For the reasons of this difference, metabolic rate, stability in blood, binding ability to DBP, and other unknown factors affect to the activity of in vivo study. 10,31) In addition, calcemic action, immunosupressive effect, and so on would be provoked when vitamin D analogues are administrated to animal host.…”
Section: Discussionmentioning
confidence: 99%
“…28) Many vitamin D analogues showed anti-cancer activity in vitro using human cultured cell lines, however, some of them did not possess such activity in vivo. 29,30) For the reasons of this difference, metabolic rate, stability in blood, binding ability to DBP, and other unknown factors affect to the activity of in vivo study. 10,31) In addition, calcemic action, immunosupressive effect, and so on would be provoked when vitamin D analogues are administrated to animal host.…”
Section: Discussionmentioning
confidence: 99%
“…La 1,25-(OH)2D inhibe la prolifération de ces cellules en les bloquant en phase G1, via un effet activateur sur la synthèse des protéines p21 et p27 [9], module la production et l'action de proto-oncogènes, dont c-myc et c-fos, et favorise l'apoptose de certaines lignées tumorales en inhibant la production de la protéine Bcl-2 [10]. À ces effets positifs sur la prolifération-différenciation cellulaire s'ajoutent d'autres effets qui concourent à l'action antitumorale de la vitamine D, comme l'inhibition de l'angiogenèse péri-tumorale et celle du développement de métastases [11].…”
Section: Vitamine D Un Facteur Anti-cancéreux ?unclassified
“…Cependant, comme pour le traitement du psoriasis, l'application de ces résultats en clinique humaine est limitée par l'hypercalcémie résultant des fortes doses de 1,25-(OH)2D requises. Parmi les nombreux analogues peu hypercalcémiants de la vitamine D, plusieurs paraissent capables de prévenir ou retarder l'évolution de leucémies ou de cancers [2,10,11]. Ils sont donc de bons candidats pour une éventuelle utilisation en clinique humaine.…”
Section: Vitamine D Un Facteur Anti-cancéreux ?unclassified
“…The classic role of 1,25-dihydroxyvitamin D 3 (1,25-(OH) 2 D 3 ) 1 includes regulating the expression of genes involved in calcium and bone metabolism (1). In addition, the hormone is an important mediator of cell growth and differentiation (2,3).…”
mentioning
confidence: 99%
“…In addition, the hormone is an important mediator of cell growth and differentiation (2,3). In a large number of 1,25-(OH) 2 D 3 -dependent target genes, distinct vitamin D response elements (VDREs) have been identified that are composed of two hexameric half-sites separated by three base pairs (DR3-type VDRE).…”
mentioning
confidence: 99%